Pyrotinib in the Treatment of Women With HER2-Positive Advanced Breast Cancer: A Multicenter, Prospective, Real-World Study - Zhang, Lili; Wu, Xiaohong; Zhou, Jun; Zhu, Mingzhen; Yu, Hao; Zhang, Yusong; Zhao, Yutian; Han, Zhengxiang; Guo, Yujiang; Guan, Xiaoqing; Wang, Xufen; Xu, Hong; et al. (Frontiers in Oncology, 2021)
Background HER2-positive breast cancer was aggressive, resulting in a poorer prognosis. This multicenter study analyzed the real-world data of women treated with pyrotinib-based therapy, aiming to describe their characteristics, treatment regimens, and to investigate the clinical outcomes. Methods A total of 141 patients with HER2-positive breast cancer were enrolled from February 2019 to April 2020. Last follow-up time was February 2021. All patients were treated with pyrotinib-based therapy in 21-day cycles. The primary endpoint was progression-free survival (PFS). Results The median PFS (mPFS) for pyrotinib-based therapy was 12.0 months (95%CI 8.1-17.8) in all patients. Among the patients with liver metastases, mPFS was 8.7 months (95%CI, 6.3-15.4) compared to 12.3 months (95%CI, 8.8-23.3) for patients without liver metastases (P=0.172). In addition, patients receiving pyrotinib-based therapy as their >2 lines treatment had a numerically lower mPFS than those receiving pyrotinib-based therapy as their ≤2 lines treatment [8.4 (95%CI, 5.9-15.4) vs. 15.1 (95%CI, 9.3-22.9) months, P=0.107]. The mPFS was 12.2 months (95%CI, 7.9-18.8) in patients with previous exposure to trastuzumab and 11.8 months (95%CI, 6.8-22.9) in patients without previous exposure to trastuzumab (P=0.732). Moreover, mPFS in patients receiving regimens with and without capecitabine were 15.1 months (95%CI, 10.0-18.8) and 8.4 months (95%CI, 6.7-22.9), respectively (P=0.070). Furthermore, in patients with brain metastases, estimated 6-month PFS rate was 70.0%, and rate at 12 months was 60.0%. Seventy patients with measurable lesions were evaluable for response. The objective response rate was 38.6% and disease control rate was 85.7%. The most common adverse event was diarrhea (85.0%). Conclusion Pyrotinib-based therapy showed promising efficacy in patients with HER2-positive breast cancer and was well tolerated, especially in patients treated with pyrotinib as ≤2 lines treatment and receiving regimens with capecitabine. The results of this real-world study further confirmed the intriguing efficacy of pyrotinib.